2004
DOI: 10.1111/j.1468-1293.2004.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicentre study of discontinuing prophylaxis for opportunistic infections after effective antiretroviral therapy

Abstract: ObjectiveTo assess the medium-term safety of discontinuing prophylaxis (primary or secondary) for opportunistic infections following an effective response to antiretroviral therapy. MethodsParticipating clinical sites prospectively identified patients in whom the discontinuation of prophylaxis for any opportunistic infection was considered to be clinically indicated, although CD4 levels were not predefined. A follow-up report was subsequently sent every 6 months requesting information on changes in prophylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The incidence rate of pneumocystosis following discontinuation of primary and secondary prophylaxis among HIV-infected patients when their CD4 counts increased to ≧200 cells/μL after receiving HAART in published studies ranges from 0 to 2.27 cases per 100 PY of follow-up, depending on the types of study design and observation duration [3,11,15-25]. In our patients who followed the guidelines for discontinuation of pneumocystosis prophylaxis, the overall incidence was 0.45 per 100 PY (95% CI, 0.05, 1.63), which is within the range of reported incidence rates of case series and cohort studies (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of pneumocystosis following discontinuation of primary and secondary prophylaxis among HIV-infected patients when their CD4 counts increased to ≧200 cells/μL after receiving HAART in published studies ranges from 0 to 2.27 cases per 100 PY of follow-up, depending on the types of study design and observation duration [3,11,15-25]. In our patients who followed the guidelines for discontinuation of pneumocystosis prophylaxis, the overall incidence was 0.45 per 100 PY (95% CI, 0.05, 1.63), which is within the range of reported incidence rates of case series and cohort studies (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…With the widespread use of highly active antiretroviral therapy (HAART) after 1996, HIV-related mortality and the risks of several major opportunistic infections, such as Pneumocystis jirovecii pneumonia (formerly P. carinii pneumonia), disseminated Mycobacterium avium complex infection, and cytomegalovirus diseases, have significantly declined in patients receiving HAART [1-3]. For example, an incidence rate of 20 cases of pneumocystosis per 100 person-months was reported in the pre-HAART era [4], which decreased to 1.2 cases per 100 person-years (100 PY) of follow-up in the era of antimicrobial prophylaxis for pneumocystosis and HAART [5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies around the world on HIVprevalent cohorts have reported and described, in detail, the spectrum of OIs worldwide, including India (Ghate et al, 2009;Vajpayee, Kanswal, Seth, & Wig, 2003;Wadhwa, Kaur, Agarwal, Jain, & Bhalla, 2007). After the advent of highly active anti-retroviral therapy (HAART), mortality and the risks of several major OIs in HIV patients, such as Pneumocystis jiroveci pneumonia (formerly Pneumocystis carinii pneumonia), disseminated Mycobacterium avium complex infection, and cytomegalovirus diseases, have significantly declined in patients receiving HAART (Brooks, Song, Hanson, Wolfe, & Swerdlow, 2005;Green Hay, Dunn, McCormack, & STOPIT Investigators, 2004;Karakousis, Moore, & Chaisson, 2004). A major problem, however, is that every individual who is eligible to receive ART cannot be covered, and those who are not covered, are unlikely to be able to afford the drugs on their own.…”
Section: Introductionmentioning
confidence: 97%
“…With PCP, the threshold level for prophylaxis is a CD4+ count of 200; much greater improvements in CD4+ number need to be gained before a reduction in risk is achieved. The supporting clinical evidence for these improvements was found by Green and colleagues who were able to demonstrate the safety of discontinuing prophylaxis for PCP, MAC and CMV in patients with HIV taking HAART [19]. In 2002, these observations were incorporated into recommendations to discontinue primary and secondary PCP prophylaxis for patients receiving HAART who have CD4 counts above 200 for 3 months or more [20].…”
mentioning
confidence: 96%